Detection of point mutations on 23S rRNA of Helicobacter pylori and resistance to clarithromycin with PCR-RFLP in gastric biopsy specimens in Mersin, Turkey - Orhan SEZGİN,; Gönül ASLAN,; Engin ALTINTAŞ,; Seda TEZCAN,; Mehmet Sami SERİN,; Gürol EMEKDAŞ, (Turkish Journal of Gastroenterology, 2019)
-